Inflammatory bowel disease and risk of dementia: An updated meta-analysis - Liu, Nanyang; Wang, Yi; He, Lanye; Sun, Jiahui; Wang, Xing; Li, Hao (Frontiers in Aging Neuroscience, 2022)
Background: Growing evidence suggests that inflammatory bowel disease (IBD) and dementia share pathological mechanisms and pathogenic risk factors. However, the previously diagnosed IBD and the subsequent risk of developing dementia are largely unknown. Aim: The purpose of this review is to assess the association between IBD and subsequent dementia diagnosis. Method: We searched PubMed, Embase, and Cochrane library from database inception to February 1, 2022. Two reviewers independently extracted data and assessed methodological quality and risk of bias. Observational study that reported the possibility of dementia in IBD and non-IBD populations were included. Eligible studies were pooled effect estimates for relative risk (RR) through fixed-or random-effects models as appropriate. Results: More than 3,181,549 participants from nine studies met the inclusion criteria. Previous IBD diagnosis did not increased the risk of subsequent all-cause dementia (RR, 1.32; 95% CI, 0.98-1.77) and AD-dementia (RR, 1.62; 95% CI, 0.96-2.76). Subgroup analyses based on study design indicated that cohort study (RR, 1.30; 95% CI, 1.09-1.55) reported an increased risk of all-cause dementia, but were not applicable to AD-dementia (RR, 1.27; 95% CI, 0.94-1.72). Positive associations between IBD patients and all-cause dementia did not differ by age and gender in cohort studies. Both ulcerative colitis (RR, 1.39; 95% CI, 1.00-1.94) and Crohn's disease (RR, 1.46; 95% CI, 1.08-1.98) are associated with increased risk of all-cause dementia. Conclusions: Evidence regarding dementia risk assessment in IBD patients is conflicting, which may be influenced by study design. More prospective cohort studies are needed to determine their relationship.